EAST JAVA’S PRODUCTIVITY GROWTH: EVIDENCE OF INDUSTRIALIZATION OR DEINDUSTRIALIZATION IN THE JAVA ISLAND? - Miguel Angel Esquivias Padilla (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2018)
This study estimates Technical Efficiency (TE) and Total Factor Productivity (TFP) to analyze the sources of growth in the province of East Java in Indonesia. Technological progress, technical efficiency change, and scale effects are estimated through a stochastic frontier analysis (SFA) to break up different sources of growth within manufacture. This study looks at patterns of output expansion by differentiating gains from conventional sources –input growth and technological progress- and non-conventional sources –technical efficiency change and scale effects-. Results are aggregated based on tech-intensity, firm size, capital to output ratio employed, and labor skills. It also compares East Java with the other five provinces in the Java Island, the manufacturing corridor of the country. As expected, manufacturing sector is growing through input growth effects and tech progress-conventional sources- but underperforming in productivity by having negative efficiency change and negative scale effects. Labor has the largest elasticity to output (0.436), capital and raw materials have a much lower elasticity, and energy has a large negative one (-3.097) also causing a sharp increase in the cost of production. Low-tech firms, higher skills, and medium in size perform 72% better than average (TFP). MLT firms with labor-intensive and medium-size firms perform 58% better than average. However, champion industries have lower skills, good access to materials, and are less intensive in energy use. Some features of firm performance are: firm with larger portions of human skills capture the largest TE and higher TP values; those under high skills report larger losses due to negative scale effects; labor-intensive firms have larger TFP (less efficient but less exposed to energy prices).